Design and implementation of a persistent multimedia object-oriented storage system. - Li, Jie. (University of Ottawa (Canada), 1995)
Multimedia information requires novel database architecture and models for its efficient storage, manipulation, retrieval, and playback. Multimedia database systems must provide facilities to model complex objects, manage the temporal relationships among different media and guarantee the synchronization as well as the continuity requirements during retrieval. In this thesis, we investigate the object-oriented database concepts and their ability to support multimedia applications and more specifically the support of real time audio/video media. A number of multimedia characteristics and requirements are analyzed and identified. Motivated by the challenge to meet the requirements, a Persistent Multimedia Object-oriented Storage System called MEDIASTORE is designed and implemented using an object-oriented database model for the management of multimedia document. A multimedia document architecture is used by MEDIASTORE to describe and model complex objects such as audio, video, image, and text. The temporal and spatial relationships between objects are also described in the document. A synchronized retrieval algorithm for playback of multimedia document is presented. The algorithm pays great attention to various unique synchronization requirements in retrieval and playback of multimedia documents. As part of an advanced multimedia OODBMS, MEDIASTORE is rich in features for the storage and manipulation of document. Amongst the features is its Graphical User Interface (GUI). The design and implementation of the GUI for MEDIASTORE is presented. Given the ever evolving nature of multimedia requirements and the time limit on this work, MEDIASTORE is far from perfect. Future trends and work are also presented.
Keywords: Engineering, Electronics and Electrical.